Agricultural Research and Innovation Systems in Transition. (16th April 2013) - Moreddu, Catherine; Poppe, Krijn J.
summary Agricultural Research and Innovation Systems in Transition Agricultural knowledge and innovation systems (AKIS) are in transition in many countries from a linear, top‐down approach towards more flexible and interactive arrangements. This transition to a system more responsive to changing demands seeks to improve the adoption of innovation in order to strengthen the competitiveness of the agri‐food sector. This article focuses on the research and innovation components of the AKIS to analyse the main developments of recent years and their drivers. It concludes that the diversity of institutional arrangements and priorities is likely to persist as they are path dependent and respond to different socio‐economic contexts. This article suggests how national governments could foster innovation in the agri‐food sector by considering a whole range of policies and improving their coherence. One suggestion is that the European Union play a role in coordinating (basic) science and research infrastructure, manage spillovers between EU regions, as well as promoting market‐based instruments, support capacity‐building and international exchange of staff, provide information using modern Information and Communication Technologies and guidelines for the evaluation of AKIS, and create a forum to exchange experiences.